Control y Biología del Helecho Trepador Japonés (Lygodium japonicum) - Patrick J. Minogue; Daniela Chevasco; Francisco Escobedo; Kimberly K. Bohn (EDIS)
This 7-page Spanish-language fact sheet describes this non-native, invasive vine which is widespread in damp areas in North and West Florida — its biology and control measures. Written by Patrick J. Minogue, Daniela Chevasco, Francisco Escobedo, and Kimberly K. Bohn and published by the UF Department of School of Forest Resources and Conservation, December 2010.